2018
DOI: 10.1016/j.jid.2017.09.036
|View full text |Cite|
|
Sign up to set email alerts
|

Indoleamine 2,3-Dioxygenase Expression in Primary Cutaneous Melanoma Correlates with Breslow Thickness and Is of Significant Prognostic Value for Progression-Free Survival

Abstract: The enzyme indoleamine 2,3-dioxygenase (IDO) is emerging as a facilitator of cancer development through its effects on cancer-associated inflammation. Recent studies report a significant improvement of the response rates in melanoma patients to PD-1 antibodies when IDO inhibitors were added to the regimen. Data on IDO expression in primary human melanomas are, however, incomplete and conflicting. Here, we show that the level of IDO expression in primary human melanoma cells significantly correlates with Breslo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 40 publications
2
43
4
Order By: Relevance
“…Interestingly, our data showed that the frequency of the IDO expression in tumors was lower in acral and mucosal melanomas than the reported frequency in cutaneous melanomas . The genetic differences between acral and mucosal melanomas and cutaneous melanomas may contribute to the IDO expression levels in tumors and in the peritumoral stroma.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…Interestingly, our data showed that the frequency of the IDO expression in tumors was lower in acral and mucosal melanomas than the reported frequency in cutaneous melanomas . The genetic differences between acral and mucosal melanomas and cutaneous melanomas may contribute to the IDO expression levels in tumors and in the peritumoral stroma.…”
Section: Discussioncontrasting
confidence: 52%
“…There are conflicting reports regarding the relevance of IDO as a biomarker. A recent study demonstrated that the IDO expression in cutaneous melanoma was correlated with shorter PFS . Another study found that endothelial expression of IDO was correlated with shorter overall survival .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, in breast carcinoma, early stage cervical cancer, and melanoma, IDO1 expression is accompany the host antitumor immune response, and it tends to positively correlate with survival . However, in another study, the high inductive IDO1 expression in primary melanoma negatively affected progression‐free survival . Under the heterogeneity of tumor gene mutations and the tumor microenvironment, both constitutive and inducible IDO1 expression can co‐exist regulated by tumor intrinsic and extrinsic mechanisms, reflecting either the absence or presence of antitumor immunity in specific tumor microenvironments.…”
Section: Introductionmentioning
confidence: 91%